The fate of germ cells in cryptorchid testis - Thorup, Jorgen; Hildorf, Simone; Hildorf, Andrea E.; Baastrup, Jonas M.; Mamsen, Linn Salto; Andersen, Claus Yding; Olsen, Tina E.; Cortes, Dina (Frontiers in Endocrinology, 2024)
Cryptorchidism in males constitutes a notable risk factor for both infertility and testicular cancer. Infertility in adulthood is closely linked to the germ cell status in childhood. Furthermore, the significance of germ cell status is important as more than 95 % of all reported testicular malignancies are germ cell tumors. The review aims to elucidate the pathogenesis of germ cells in cryptorchid testes concerning their association with infertility and testicular malignancies.Impaired germ cell numbers are evident in cryptorchid testes even during antenatal and neonatal stages. In cryptorchidism there is a rapid decline in germ cell number within the first year of life, partially attributed to physiologic gonocyte apoptosis. Additionally, germ cells fail to differentiate normally during mini-puberty leading to reduced germ cell proliferation and delayed clearance of gonocytes from the seminiferous epithelium. Absence of germ cells in testicular biopsies occurs already 10 months of age and germ cell deterioration progressively worsens with approximately 50% of persisting cryptorchid testes lacking germ cells during puberty. The deficient germ cell maturation and proliferation leads to later infertility. Elevated temperature in the cryptorchid testes and also hormonal deficiency contribute to this phenomenon.Germ cell neoplasia in situ (GCNIS) originating during fetal development may manifest in rare cases associated with disorders of sexual development, chromosomal abnormalities in boys, specific syndromes, and teratomas that include cryptorchidism. In adults, the presence of GCNIS predominantly represents a new histology pattern before invasive germ cell cancer is demonstrated and is neither congenital nor related to abnormal gonocyte transformation.